Behavior of university students in the health area regarding the use of medicines and the practice of self-medication (Research, Society and Development, 2022)
The practice of self-medication is a common behavior in several population groups, including university students. In this context, the objective of this study was to verify the behavior of university students in the health area in relation to the use of medication, particularly the practice of self-medication. This is a descriptive, observational, cross-sectional epidemiological study carried out by evaluating the practice of self-medication among university students. Questionnaires containing sociodemographic and other questions related to the practice of self-medication were used. The results obtained in this study showed that the majority of those investigated were ≤ 29 years old (87.6%), were female (81.9%), of non-white skin color (74.6%), without a steady partner (51.8%) and lived with family members (81.9%). Regarding schooling, 88.1% had incomplete higher education, had ≥ 2.5 years of education and received ≤ 2 salaries (58.2%). It was observed that the most used drug class were anti-influenza drugs (87%), and only (9.3%) had adverse reactions. The symptom responsible for most cases of self-medication was headache/fever (61.1%), followed by cold/flu (89.1%), menstrual cramps (69.9%) and stomach pain/bad digestion (62.1%). The consumption of non-prescribed medication occurred in 54.9% of the cases, on its own. Thus, it is concluded that educational practices in higher education institutions about the risk of self-medication are necessary in order to sensitize university students about the risks of self-medication.